Digital infrastructure construction and urban green transition: A quasi-natural experiment based on the broadband China policy using double machine learning - Tiangui Lv; Xianzhe Huang; Menghan Yuan; Gui Jin; Qiao Zhao; Shufei Fu (Sustainable Cities and Society, 2026)

Constraint or promotion? Revealing linkages between environmental regulation and green technology diffusion in the Yangtze River Delta Urban Agglomeration - Tiangui Lv; Qiao Zhao; Gui Jin; Shufei Fu; Anying Chen (Environment, Development and Sustainability, 2026)

Decrypting spatiotemporal evolution and influencing factors of cultivated land use carbon compensation in the middle reaches of Yangtze River: An interpretable machine learning approach - Tiangui Lv; Menghan Yuan; Qiao Zhao; Xianzhe Huang; Shufei Fu; Wang Li (Journal for Nature Conservation, 2026)

Driving factors and multi-scenario simulation of ecological resilience in the middle reaches of the Yangtze river metropolitan area - Shufei Fu; Yishen Liao; Tiangui Lv; Qiao Zhao; Anying Chen; Menghan Yuan; Chunguang Hu; Houbao Fan (Environment, Development and Sustainability, 2026)

Discerning changes in carbon emission intensity of cultivated land utilization since agricultural green transformation: Based on the motivation-opportunity-ability (MOA) framework - Shufei Fu; Tiangui Lv; Guangdong Wu; Hongyi Li; Limeng Zhu; Xinmin Zhang (Environmental Impact Assessment Review, 2025)

Exploring the impact of the digital economy on carbon emission intensity: A case study of the urban agglomeration in the middle reaches of the Yangtze River - Tiangui Lv; Can Geng; Shufei Fu; Qiao Zhao; Han Hu; Xinmin Zhang (Environment, Development and Sustainability, 2025)

Deciphering flows: Spatial correlation characteristics and factors influencing carbon emission intensity in the Yangtze River Delta - Tiangui Lv; Qiao Zhao; Shufei Fu; Gui Jin; Xinmin Zhang; Han Hu; Guoliang Xu (Journal of Cleaner Production, 2024)

Impact of the intensive use of urban construction land on carbon emission efficiency: evidence from the urban agglomeration in the middle reaches of the Yangtze River - Tiangui Lv; Can Geng; Xinmin Zhang; Zeying Li; Han Hu; Shufei Fu (Environmental Science and Pollution Research, 2023)

Spatiotemporal evolution and convergence of agricultural eco-efficiency in the middle reaches of the Yangtze River - Tiangui Lv; Shufei Fu; Xinmin Zhang; Han Hu; Yanwei Zhang (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Driving mechanism of the allometric relationship between economic development and carbon emissions in the Yangtze River Delta urban agglomeration, China - Tiangui Lv; Han Hu; Xinmin Zhang; Lu Sun; Zhaoling Li; Yijing Chen; Shufei Fu (Environment, Development and Sustainability, 2023)

Seven undescribed compounds from the flower heads of Helianthus annuus L. - Jiaxuan Bai; Xianmei Piao; Yanli Wang; Xiaoling Cheng; Mingfeng Feng; Yongming Wang; Rong Fu; Jinna Zhao; Shufei Yu; Ze Li; Libo Wang; Jian Huang; et al. (Phytochemistry, 2023)

Vocalization Behavior of Chinese Bahaba (Bahaba taipingensis) during the Reproduction Season - Hongquan Li; Zhongchang Song; Jiangang Hui; Yingnan Su; Weijie Fu; Shufei Zhang; Lin Yan; Kuoqiu Yan; Honghui Huang; Yu Zhang (Journal of Marine Science and Engineering, 2023)
Chinese bahaba (Bahaba taipingensis) is a critically endangered fish species, which can produce sounds like other Sciaenidae species. In this study, sounds produced by sexually mature Chinese bahaba were recorded during the reproduction season for the first time. Two distinct types of sounds were observed during the reproduction season, termed as single drum and fast drum trains calls. Single drum callings occurred as a series of trains with rapid pulses, while fast drum trains callings were mainly made of a single signal. The single drum and fast drum trains had a peak frequency of 77.8 ± 16.2 Hz and 79.1 ± 8.7 Hz, respectively. Statistical analysis suggested significant differences in −3 dB bandwidth, signal duration, and root-mean-square sound pressure levels, except for peak frequency (p

Spatiotemporal heterogeneity and decoupling decomposition of industrial carbon emissions in the Yangtze River Delta urban agglomeration of China - Han Hu; Tiangui Lv; Xinmin Zhang; Hualin Xie; Shufei Fu; Can Geng; Zeying Li (Environmental Science and Pollution Research, 2023)

Spatiotemporal coupling of multidimensional urbanization and resource–environment performance in the Yangtze River Delta urban agglomeration of China - Han Hu; Tiangui Lv; Xinmin Zhang; Hualin Xie; Shufei Fu; Li Wang (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Spatiotemporal dynamics and decoupling mechanism of economic growth and carbon emissions in an urban agglomeration of China - Han Hu; Tiangui Lv; Xinmin Zhang; Shufei Fu; Can Geng; Zeying Li (Environmental Monitoring and Assessment, 2022)

Spatiotemporal pattern of regional carbon emissions and its influencing factors in the Yangtze River Delta urban agglomeration of China - Tiangui Lv; Han Hu; Xinmin Zhang; Hualin Xie; Shufei Fu; Li Wang (Environmental Monitoring and Assessment, 2022)

Spatial spillover effects of urbanization on carbon emissions in the Yangtze River Delta urban agglomeration, China - Tiangui Lv; Han Hu; Xinmin Zhang; Hualin Xie; Li Wang; Shufei Fu (Environmental Science and Pollution Research, 2022)